Chemistry laboratory management: Reviewing planning, organization, and evaluation for effectiveness - Deny Hadi Siswanto; Helena Anggraeni Putri; Kintoko Kintoko; Suwajirah Suwajirah (Universitas Pendidikan Indonesia, 2025)
Chemistry laboratory management at SMA Dr. Wahidin is important in supporting learning. This research aims to describe chemistry laboratory management using a qualitative descriptive approach. Research subjects included school principals, deputy heads of curriculum, laboratory assistants, technicians, and chemistry teachers. Data was collected through observation, interviews, and documentation. The research results show that laboratory work program planning is prepared systematically by the head of the laboratory, including vision, mission, and long and short-term plans. The organizational structure involves various parties, including school principals, laboratory assistants, technicians, and chemistry teachers. The school principal plays a role in organizing and supporting laboratory management to be more optimal. The implementation of the work program went according to plan. However, coordination between parties still requires improvement. Apart from that, supervision and evaluation carried out by school principals need to be further improved so that the effectiveness of laboratory management is more optimal. Abstrak Manajemen laboratorium kimia di SMA Dr. Wahidin berperan penting dalam mendukung pembelajaran. Penelitian ini bertujuan untuk mendeskripsikan manajemen laboratorium kimia dengan pendekatan deskriptif kualitatif. Subjek penelitian meliputi kepala sekolah, wakil kepala bidang kurikulum, laboran, teknisi, dan guru kimia. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa perencanaan program kerja laboratorium disusun secara sistematis oleh kepala laboratorium, mencakup visi, misi, serta rencana jangka panjang dan pendek. Struktur organisasi melibatkan berbagai pihak, termasuk kepala sekolah, laboran, teknisi, dan guru kimia. Kepala sekolah berperan dalam pengorganisasian guna mendukung pengelolaan laboratorium agar lebih optimal. Pelaksanaan program kerja telah berjalan sesuai rencana, namun koordinasi antar pihak masih memerlukan peningkatan. Selain itu, pengawasan dan evaluasi yang dilakukan oleh kepala sekolah perlu lebih ditingkatkan agar efektivitas pengelolaan laboratorium semakin optimal. Kata Kunci: laboratorium Kimia; manajemen; sekolah menengah atas